Prepubertal castration causes the age‐dependent changes in hippocampal long‐term potentiation. Issue 5 (14th February 2013) - Moradpour, Farshad; Fathollahi, Yaghoub; Naghdi, Nasser; Hosseinmardi, Nargess; Javan, Mohammad
<x xml:space="preserve">Abstract</x> The effects of prepubertal castration on hippocampal CA3‐CA1 synaptic transmission and plasticity were studied at different ages in vitro. The field excitatory postsynaptic potentials (fEPSP) and population spikes (PS) were simultaneously recorded from stratum radiatum and stratum pylamidale of area CA1 following stimulation of Schaffer collaterals in slices taken from sham‐castrated and castrated rats at postnatal days (PND) 28, 35, 45, and 60. Castration had no effect on baseline responses at different ages except at PND 60 that a decrease in the fEPSP slope was seen. Prepubertal castration caused age‐specific changes in CA1‐long term potentiation (LTP) induction. The castration did decrease both fEPSP‐LTP and PS‐LTP at PND 35 but a decrease was seen only in PS‐LTP at PND 60. NMDA receptor antagonist AP5 (25 µM) completely blocked both fEPSP‐LTP and PS‐LTP at PND 60 and only PS‐LTP at PND 35 in both sham‐castrated and castrated groups. Although AP5 blocked fEPSP‐LTP at PND 35 in sham‐castrated group, it failed to inhibit fEPSP‐LTP at PND 35 in castrated one. These findings suggest that prepubertal castration causes the age‐dependent changes in CA1‐LTP induction, which might arise from alterations in the NMDA receptors. Synapse 67:235–244, 2013. © 2013 Wiley Periodicals, Inc.